Over a million students use our free study notes to help them with their homework
First, separate the algebraic fraction:(x+7) / ((x-3)(x+1)2 = A/(x+3) + B/(x+1) + C/(x+1)2 Multiply both sides by (x-3)(x+1)2: (x+7) = A(x+1)2+ B(x+1)(x+3) + C(...
This is usually a good idea if you have an integral with two functions multiplied together when one of the functions differentiates to a constant (could take more than one differentiation).For example to ...
Where does the circle (x-6)2+(y-7)2=4 intersect with y=x+3We need to sub y=x+3 into the circle equation giving us an equation in just x:(x-6)2+(x-4)2=4Next we e...
Part 1: This question requires us to first do some rearranging. The right hand side of the equation is in terms of h, and we are looking to find t in terms of h, so it won't be appropriate to simply integ...
Firstly, we must use the special property of trig functions which means that (sinx)n is the same as sinnx. Likewise, (cosx)n=cosnx, (tanx)n=tann...
←
180
181
182
183
184
→
Internet Safety
Payment Security
Cyber
Essentials